PHONOLOGY OF MOOI LANGUAGE - Novaria Panggabean (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
Mooi is one of the local languages ​​in Papua. Mooi language ​​belongs to the Non-Austronesian language group. This research discusses about Mooi language phonology, including Mooi language phonemes, their distribution and phonotactics. Mooi language has 26 segregated phonemes consisting of 18 consonants, 8 vocals (monophtong), and 4 diphthongs. The phonemes are:/p/, /b/, /t/, /d/, /k/, /s/, /f/, /g/, /S/, /h/, /k/, /l/, /r/, /m/, /n/, /G/, / ñ /, /y/, /w/, /a/, /i/, /u/, /e/, /o/, /|/, / O /, and /|/.